# equivalence of t-test and F-test in ANOVA

#### rayuk

##### New Member
Something about ANOVA is confusing me. Say you have a regression model:

y = b0 + b1*x1 (where b0 and b1 are coefficients and x1 is an explanatory variable)

and want to do an F-test on the null hypothesis, b2 = 0 (ie "should I include explanatory variable x2 in my model?")

Is this F-test not equivalent to actually calculating the coefficients for the model:

y = b0 + b1*x1 + b2*x2

and performing a t-test based on the null hypothesis b2 = 0 ?

Last edited:

#### Dragan

##### Super Moderator
Something about ANOVA is confusing me. Say you have a regression model:

y = b0 + b1*x1 (where b0 and b1 are coefficients and x1 is an explanatory variable)

and want to do an F-test on the null hypothesis, b2 = 0 (ie "should I include explanatory variable x2 in my model?")

Is this F-test not equivalent to actually calculating the coefficients for the model:

y = b0 + b1*x1 + b2*x2

and performing a t-test based on the null hypothesis b2 = 0 ?
There are two F-tests: One for the full model (that includes both X1 and X2 that tests the null hypothesis that b1 = b2 = 0) and another one that could be computed to test for the incremental increase in R^2 associated with including X2 (b2 =0).

The latter is as you state: the F test is the square of the t-test for the null hypothesis that b2 = 0.

#### rayuk

##### New Member
There are two F-tests: One for the full model (that includes both X1 and X2 that tests the null hypothesis that b1 = b2 = 0) and another one that could be computed to test for the incremental increase in R^2 associated with including X2 (b2 =0).

The latter is as you state: the F test is the square of the t-test for the null hypothesis that b2 = 0.
Hi Dragon,